Antioxidant and anti-adipogenic activities of Momordica cochinchinensis (Lour). Spreng fruit extracts - Abdul Rahman, Mohd Nazri; Ismail, Amin; Azlan, Azrina; Abdul Aziz, Ahmad Fazli; Muhammad, Nor Hayati (Universiti Putra Malaysia Press, 2024)
Introduction: Momordica cochinchinensis (Lour) Spreng, known as gac fruit, is rich in bioactive compounds like carotenoids (β-carotene, lycopene, and lutein). This study assessed the antioxidant, cytotoxic, and anti-adipogenic properties of gac fruit extracts (GFE) from different fractions (peel, pulp, aril), using 3T3-L1 adipocytes. Method: Gac extracts’ DPPH radical scavenging was tested with 1000µg/mL dilutions. 3T3-L1 pre-adipocyte viability was measured via MTT assay. Differentiated adipocytes were treated (75, 150, 300 µg/mL) with GFE for 7 days. Inhibitory effects on adipogenesis and lipid accumulation were studied through Oil Red O staining. Triglyceride content was quantified and compared to controls. Results: IC50 values against DPPH radicals were 660µg/mL (peel), 560µg/ mL (pulp), and 820µg/mL (aril). 3T3-L1 cell viability was unaffected up to 200µg/mL. However, 200µg/mL GFE decreased viability, inhibiting growth. Gac extracts effectively reduced lipid accumulation and hindered cell differentiation dose-dependently. Pulp extract notably reduced intracellular triglycerides, surpassing aril and peel effects. Conclusion: Gac fruit extract fractions (peel, pulp, and aril) efficiently inhibited adipogenesis in 3T3-L1 cells, evidenced by lowered lipid accumulation, triglyceride content, and cell viability. This study highlights gac fruit extracts’ potential therapeutic use against obesity.